Diagnosis and Management of Hepatitis in Patients on Checkpoint Blockade. (31st May 2018) - Reynolds, Kerry; Thomas, Molly; Dougan, Michael
Abstract: : Many human tumors are recognized by the adaptive immune system, but these spontaneous antitumor responses are typically inadequate to mediate regression. Blockade of immune regulatory "checkpoint" receptors such as cytotoxic T‐lymphocyte‐associated antigen 4 and programmed cell death 1 can unleash antitumor immunity, resulting in tumor responses that can be durable. Alongside the enormous promise of immunotherapy for cancer, the immune dysregulation of checkpoint blockade has led to a plethora of new autoimmune adverse events. Hepatic toxicity occurs in 1%–17% of patients on immune checkpoint inhibitors, with the precise incidence dependent on both the drug used and the underlying malignancy. Hepatitis is most commonly a low‐grade toxicity, but grade 3 and 4 hepatotoxicity does occur. Here we will answer frequently asked questions regarding immune‐related hepatitis to assist in the recognition and management of this important condition. Key Points: Immune related hepatitis is a potentially serious complication of checkpoint blockade. The differential for elevated liver function tests in patients on checkpoint blockade is broad. Diagnostic testing such as viral serologies, liver ultrasound, cross sectional imaging, and liver biopsy may help in the diagnosis of immune related hepatitis in select patients. Patients with underlying cirrhosis are an at risk population for whom current grading criteria may underestimate the severity of liver inflammation. Severe immune related hepatitis is best managed by a multi‐disciplinary team that includes a hepatologist. Most patients with immune related hepatitis respond to corticosteroids, but a substantial fraction require treatment with a secondary immunosuppressive agent. Abstract : Immunotherapy for cancer holds great promise, but immune dysregulation of checkpoint blockade has resulted in new autoimmune adverse events. Hepatic toxicity occurs in 1%–17% of patients on immune checkpoint inhibitors. Hepatitis is usually a low‐grade toxicity, but grade 3 and 4 hepatotoxicity does occur. This article answers frequently asked questions about immune‐related hepatitis to assist in the recognition and management of this important condition.